Inventarisasi Jenis Burung Di Habitat Hutan Desa Waai Kabupaten Maluku Tengah - Veince Benjamin Silahooy; Laury Marcia Chara Huwae; Kresyan Pentury (Program Studi Pendidikan Biologi, FKIP Unpas,, 2020)
Birds are an important component in a forest ecosystem. Birds play a role in pollination, seed dispersers, pest control, and even their droppings provide nutrients for the soil. After the earthquake in Ambon and surrounding areas in September 2019, many people fled to the forest. This research was conducted in Waai village to inventory the species of birds in the forest (HA) and forests that were converted into post-earthquake refuge (HP) using the list of bird species and natural sciences. The results show that 8 species of birds were found at the HA location while 3 species of birds were found at the HP location. The highest species abundance was Passer montanus at both locations. The lowest abundance value on HA is Todirhamphus chloris and Ducula bicolor, while on HP is Leptocoma aspasia. Diversity index analysis shows 1.67 index on HA and 0.86 on HP.